(untitled) (Bangladesh Critical Care Journal, 2014)
Sclerosing Encapsulating Peritonotis ( SEP) or Abdominal Cocoon is a rare condition characterized by total or partial encasement of the small bowel by a fibrocollagenous cocoon like sac. It was first described and named by Foo et al in 1978. Here we present a case of SEP or cocoon in a young girl with typical radiological and per operative finding. DOI: http://dx.doi.org/10.3329/bccj.v2i1.19969 Bangladesh Crit Care J March 2014; 2 (1): 42-43